CT PELVIMETRY OF VARIANT PELVIS AND CHILD BIRTH PROGNOSIS - LALEYE, C.M.; AZONBAKIN, Simon; DELMAS, Vincent; AGOSSOU-VOYEME, AUGUSTIN KARL; DOUARD, Richard; HOUNNOU, GERVAIS MARTIAL (My University, 2018)
The aim of this study was to determine the threshold values of pelvimetry by scanning and to evaluate the ability of the pelvimetry alone to diagnose a fetal-pelvic disproportion. It was an observational retrospective study on 410 pregnant women who had a scanner pelvimetry for any reasons. Based on the fetal presentations, two subgroups (breech and cephalic -others) have been defined. Measurements of the main obstetric diameters (promonto-retropubic, median transverse and dual sciatica) were taken. The 5th and 10th percentile were calculated as well as the 90th and 95th to determine the threshold values of pelvimetry by scanner. The scanner values found on CT were compared with the standard X ray pelvimetry values. Referring to extreme values obtained by pelvimetry scanner, some pathological pelvic brim were reconstructed in 3D. Moreover, the delivery prognostic was analyzed by crossing the pelvic inlet dimensions (Magnin index) and pelvic outlet dimensions (bi-sciatic diameter) with the outcome of the delivery. The mean values of the scanno-pelvimetry measurement in our series were:m12,39 cm (± 1) for the promontoretropubic diameter, 12.88 cm (± 1.01) for the transverse median diameter and 11 cm (± 1.32) for the bi-sciatic diameter. These measurements provided an accuracy less than 1 cm compared to the standard ray pelvimetry. Although Magnin index at 23 allows a vaginal delivery, 51% of oursample have failed. Moreover, for the Magnin index at 24 and 25, the vaginal delivery failure rate remains high:45.1% and 39.61% respectively. Compared to classical pelvimetry, pelvimetry by scanner provides additional precision and allows to study the geometry of the basin. However, the pelvimetry alone could not be effective to establish the prognosis of vaginal delivery.
Keywords: scanno-pelvimetry; prognosis; delivery.